Perancangan Dan Implementasi Jaringan Komputer Smk Negeri 1 Tahuna - Ray Rivay Anugrah Aer Pelealu; Djafar Wonggo; Olivia Kembuan (JOINTER : Journal of Informatics Engineering, 2020)
SMK Negeri 1 Tahuna is one of the Educational Institutions that aims to develop the potential of the nation's children so that they can compete at the world level. To meet these objectives Educational Institutions need to be equipped with adequate computer networks. This study aims to manage the computer network system in SMK Negeri 1 Tahuna so that it can be optimally utilized by teachers and students. The research method used in this study is the Network Development Life Cycle (NDLC). Steps being taken are: Analysis, Design, Prototype Simulation, Implementation, Observation, and Arrangement. There has been an increase in network quality after this study. Such as the delay value on the TKJ LAB SSID decreased by 47%, the value of packet lost by 67%, the difference in the value of downloads rose by 1.17 Mbps, the difference in the value of uploads rose by 0.99 Mbps and the delay value on the SSID SMK 1 year decreased by 47%, the value of the packet lost 33%, the difference in the value of downloads rose 0.74 Mbps, the difference in the value of uploads rose 1.75 Mbps. Keywords— design, network, NDLC